2019
DOI: 10.1111/apps.12238
|View full text |Cite
|
Sign up to set email alerts
|

No Herd for Black Sheep: A Meta‐Analytic Review of the Predictors and Outcomes of Workplace Ostracism

Abstract: Ostracism is a ubiquitous and inevitable part of human personal and professional lives. Despite its prevalence, organizational scholars have yet to provide a comprehensive review of the empirical literature on workplace ostracism. In this study, I use belongingness theory, conservation of resources theory, and need‐threat/need fortification theory to conduct a meta‐analysis of the relationships between the predictors and outcomes of workplace ostracism. My results suggest that experiences of workplace incivili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(101 citation statements)
references
References 146 publications
(241 reference statements)
1
88
0
12
Order By: Relevance
“…A study by Gjerald and Øgaard (2010) demonstrated positive correlations between job satisfaction and the competence of colleagues, as shown by their flexibility and use of initiative. However, exclusion by colleagues leads to lower satisfaction and emotional exhaustion, according to Bedi (2019). This emotional exhaustion is, in turn, negatively correlated with job satisfaction, according to Karatepe et al (2009).…”
Section: Personnel Development ("W")mentioning
confidence: 97%
“…A study by Gjerald and Øgaard (2010) demonstrated positive correlations between job satisfaction and the competence of colleagues, as shown by their flexibility and use of initiative. However, exclusion by colleagues leads to lower satisfaction and emotional exhaustion, according to Bedi (2019). This emotional exhaustion is, in turn, negatively correlated with job satisfaction, according to Karatepe et al (2009).…”
Section: Personnel Development ("W")mentioning
confidence: 97%
“…İş yeri dışlamasını etkileyen pek çok değişken olduğu gibi, onun etkilediği de pek çok değişken vardır. Ancak meta-analiz ve derleme çalışmaları bu değişkenler arasında kişilik özellikleri üzerinde özellikle durmuştur (Bedi, 2019;Howard, Cogwell, & Smith, 2019).…”
Section: Introductionunclassified
“…While most studies based on social exchange theory (Blau, 1964) have focused on positive reciprocity (Gouldner, 1960), our results indicate strong support for negative reciprocity (Bedi, 2021), such that cronyism leads to feelings of ostracism among non-cronies, and non-cronies reciprocate for these negative feelings by withholding information leading to a decline in social capital. While our results are consistent with the norm of negative reciprocity (Gouldner, 1960), future research should measure the mediating link, the extent to which respondents withheld information, between ostracism and social capital.…”
Section: Discussionmentioning
confidence: 42%
“…Second, based on the norm of negative reciprocity (Gouldner, 1960), ostracized employees will retaliate, either actively, such as engaging in counterproductive behaviors (e.g. Bedi, 2021; Peng and Zeng, 2017) or passively, such as by withholding information or effort (Greco et al , 2019). Such withholding of knowledge or information, referred to as knowledge hoarding, allows a target to negatively reciprocate less visibly, a tactic reflective of peoples' tendencies to avoid confrontation and conflict when possible (e.g.…”
Section: Theoretical Foundations and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation